2005
DOI: 10.1128/jvi.79.23.14562-14569.2005
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Interferon-Induced Apoptosis by Epstein-Barr Virus Small RNAs Is Not Mediated by Inhibition of PKR

Abstract: The Epstein-Barr virus (EBV) EBER transcripts are small, highly structured RNAs able to bind to and inhibit activation of the double-stranded RNA-dependent protein kinase PKR in cell-free systems, and within latently infected B-cell lines they inhibit alpha interferon-induced apoptosis that is believed to be mediated through PKR. Here, we address the consequences of EBER expression for PKR activation in vivo in response to alpha interferon. In agreement with published findings, either EBV infection or the EBER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 50 publications
5
52
0
Order By: Relevance
“…Indeed, chronic activation of antiviral immunity by erroneous detection of extracellular RNA drives autoimmunity in predisposed individuals (20). Although binding of proinflammatory EBERs to cytoplasmic sensors has been reported in vitro (9)(10)(11)(12), there is little evidence that this may occur in latently infected B cells in a physiologically relevant context (21), but there are multiple indications that EBERs are secreted from infected cells (9,22,23).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, chronic activation of antiviral immunity by erroneous detection of extracellular RNA drives autoimmunity in predisposed individuals (20). Although binding of proinflammatory EBERs to cytoplasmic sensors has been reported in vitro (9)(10)(11)(12), there is little evidence that this may occur in latently infected B cells in a physiologically relevant context (21), but there are multiple indications that EBERs are secreted from infected cells (9,22,23).…”
Section: Significancementioning
confidence: 99%
“…Both double-stranded loops and the uncapped 5′-triphosphate terminus of EBERs serve as ligands for pathogen recognition receptors (PRRs) (9)(10)(11)(12). Because infected individuals (estimated at 90% of the world population) generally have no symptoms, it seems that EBER production in healthy individuals elude cell-intrinsic danger signaling.…”
Section: Significancementioning
confidence: 99%
“…To support this hypothesis, researchers have made it clear that when EBV-negative Akata cells transfected with EBERs were analysed, PKR autophosphorylation in vitro was inhibited (Nanbo et al, 2002). However, Ruf reported that EBERs did posses a modest ability to protect the cell against interferon-induced apoptosis, but this process was independent of PKR-eIF-2α activation (Ruf et al, 2005). Thus Swaminathan suggested that EBERs might inhibit apoptosis while it was unlikely that inhibition of PKR was the primary mechanism for this effect (Swaminathan, 2010).…”
Section: Localization and Potential Function Of Ebers Involved Rnp Comentioning
confidence: 99%
“…Subsequent studies revealed that EBERs were responsible for these phenotypes (Komano et al, 1999;Ruf et al, 2005). Transfection of the EBER genes into EBV-negative Akata clones restored the capacity for growth in soft agar, tumorigenicity in SCID mice, resistance to apoptotic inducers, and upregulated expression of bcl-2 that was originally retained in parental EBV-positive Akata cells but lost in EBV-negative subclones.…”
Section: Ebers Associated Oncogenesis and Cell Transformationmentioning
confidence: 99%
“…[33][34][35] EBER RNAs can also inhibit apoptosis induced by various signals including IFN-a, but it remains controversial as to whether this antiapoptotic activity is mediated through the inhibition of PKR. [36][37][38] To address 1). In the second experiment, we assessed the activation of eukaryotic initiation factor 2a (eIF2a) using the pATF4-UTR-Luc reporter construct.…”
Section: Induction Of Rnai By Eber-shrna Transcriptsmentioning
confidence: 99%